Factors Affecting Thai Consumer Decisions Incentive Travel of India Tourist to Thailand - Tangtenglam, Susaraporn (Journal of Multidisciplinary in Humanities and Social Sciences, 2020)
The objectives of this research were (1) to study the factors affecting travel selection Indian tourists incentive in Thailand; and (2) to study the factors affecting the success of the service quality development Indian tourists incentive in Thailand. This research was a qualitative and quantitative methods. The sample was used to interview entrepreneurs collect data 10 participants and sample was used to questionnaire Indian tourists were 400 participants. The questionnaire responses were analyzed using frequency, percentage, and chi-square test. The research results were found as follows; The factors affecting travel selection Indian tourists incentive in Thailand. Which were the highest level ( =4.75, S.D.=0.46) when classified in each aspect by sorting the average from highest to lowest, cost of living ( = 4.81,S.D. = 0.90), meeting room ( = 4.70, S.D. = 0.77), attractions ( = 4.68, S.D. =0.57), transportation ( = 4.61, S.D.= 0.69) accommodation ( = 4.57, S.D.= 0.52) The Factors affecting success of service quality development Indian tourists incentive in Thailand. It was found that service quality development Indian tourists incentive of all 5 Indian tourists, consisted of the cost of living in relation to the quality of service. The meeting room was related to the quality of service. Tourist attractions were related to the service quality. Transportation was related to service quality. Accommodation was related to service quality. The differences were statistically significant at 0.05 level.